The Third Surprise: A Case of Nucleus and Intraocular Lens Drop with Rigid Polymethyl Methacrylate Posterior Chamber Intraocular Lens Implantation in the Anterior Chamber - Marina Ger; Megha Gulati (Delhi Journal of Ophthalmology)
Nucleus drop following a posterior capsular rent is a known complication of cataract surgery. We report a case of mismanaged cataractous lens and intraocular lens (IOL) drop in the vitreous cavity with a rigid posterior chamber IOL placed in the anterior chamber. This patient presented with secondary glaucoma. The patient was managed with the IOL explantation - both from the anterior and posterior segment and pars plana lensectomy with vitrectomy. Secondary IOL was also implanted.